Pengelolaan Kondisi Ekosistem Hutan Mangrove dan Daya Dukung Lingkungan Berbasis Masyarakat di Desa Tanggul Tlare Kecamatan Kedung Kabupaten Jepara - Bekti Utomo (VISA: Journal of Vision and Ideas, 2024)
Mangrove forest management is important in efforts to preserve the environment in coastal areas. This research aims to 1) determine the condition of mangrove forests after rehabilitation, 2) determine the impact of mangrove forest rehabilitation activities on the community, 3) determine the forms of community participation in mangrove forests, 4) determine alternative strategies for ideal mangrove forest management. This research uses a survey approach with interviews and field observations. The population is all coastal residents in the research area, the sampling technique uses “cluster random sampling”. Data collection methods used interviews and field observations, while data analysis on coastal resource management strategies was carried out using a SWOT analysis approach. The research results show that 1) the mangrove vegetation found includes 4 species from 3 families, namely the Avicenniaceae family (Avicennia marina), the Euphorbiaceae family (Excoecariaagallocha), and the Rhizophoraceae family (Rhizophoramucronata, Rhizophoraapiculata, and Bruguieragymnorizum) 2) The impact of mangrove forest rehabilitation in the area research is increasing fish catches, reducing coastal erosion, preventing sea breezes, increasing biota catches (shrimp, crabs, shellfish) on the coast, and turning the area into a tourist attraction area. 3) forms of participation in the form of thoughts amounting to (39.45%), energy (52.94%), expertise (65.91%), and goods/money (50.88%), 4) mangrove management strategy in Tanggul Tlare Village, Jepara Regency consists of 4 main priorities namely community development in carrying out planting based on existing potential, increasing socialization to the community about the dangers of careless logging of mangroves, providing counseling and outreach about the environment and mangrove ecosystems, providing outreach regarding the implementation of government regulations regarding the environment. The conclusions of this research include 1) the mangrove vegetation diversity index value in Tanggul Tlare Village, Kedung District, Jepara Regency is moderately abundant, 2) The impact of rehabilitation activities on mangrove forest management in Tanggul Tlare Village provides good and positive benefits to the community, 3) forms of participation that have been carried out by the community include thoughts, energy, contributions of expertise, and donations of goods/money, 4) community-based mangrove forest management strategies can be developed ideally and sustainably.